Effectiveness of Adjuvant Chemotherapy in Variant Histology Upper Tract Urothelial Carcinoma Following Radical Nephroureterectomy: Stabilized Inverse Probability Treatment Weighting Analysis of Single Center Experience - Park, Inkeun; Suh, Jungyo; Lim, Bumjin; Song, Cheryn; You, Dalsan; Jeong, In Gab; Hong, Jun Hyuk; Ahn, Hanjong; Cho, Yong Mee; Lee, Jaelyun; Hong, Bumsik (Clinical genitourinary cancer, 2024)
The study aimed to investigate the impact of adjuvant chemotherapy on time to recurrence (TTR) and overall survival (OS) in patients with histologic variants of upper tract urothelial carcinoma (VUTUC) following radical nephroureterectomy (RNU). A retrospective review of 131 VUTUC patients' medical records, from a pool of 368 non-metastatic localized or locally advanced UTUC cases, treated at a single tertiary referral center between January 2011 and January 2021. The intervention was adjuvant chemotherapy administration post-RNU. TTR and OS were evaluated using Kaplan-Meier and Cox proportional hazard regression, covariates adjusted for age, postoperative GFR, history of neoadjuvant chemotherapy, T and N stage with stabilized inverse probability of treatment weighting (sIPTW). The application of adjuvant chemotherapy showed a significant extension in TTR (P = .01), but no substantial impact on OS (P = .19) after sIPTW adjustment for covariates. Multivariate analysis revealed adjuvant chemotherapy, tumor size, and lymphovascular invasion as significant prognostic factors for TTR. In contrast, only tumor size and perineural invasion were significant for OS. Adjuvant chemotherapy reduced the progression risk in certain VUTUC subtypes (squamous or glandular/micropapillary), but not in sarcomatoid variants. Adjuvant chemotherapy appears to improve TTR, albeit without a significant effect on OS, in nonmetastatic localized and locally advanced VUTUC patients post-RNU. While beneficial to some VUTUC subtypes, it did not yield significant advantages for sarcomatoid variants. Despite adjustments for known confounders, the study's findings may be subject to potential selection bias and unmeasured confounding factors. This study assesses the effect of adjuvant chemotherapy on recurrence and survival in 131 patients with variant histology upper tract urothelial carcinoma (VUTUC) following surgery. Utilizing Kaplan-Meier and Cox regression with sIPTW adjustment, adjuvant chemotherapy showed a significant benefit in recurrence time but not overall survival.